Vocational Academic Choice And Students' Perceptions - Akın, Fahamet; Yıldırım, Osman (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
As it is well-known, Holland's theory of vocational choice offers a dependable framework for students' college expectations and experiences. According to Holland's theory of vocational choice, students' personally types and the factors which come from students' environment are very important regarding of the effectiveness of academic programs. In other words, there should be a kind of person-environment fit. This research aims at clarifying the relation between students' personally types and their environments by using Holland's theory of vocational choice. The research has been conducted on 246 students attending at School of Vocational Studies. According to the research findings, there are strong relationships between students' personality types, college expectations and environmental conditions.
Keywords: Holland's Theory; College Expectations; Environment; Personality Types; Hollanda'nın Kuramı; Üniversite Beklentileri; Çevre; Kişilik tipleri